Avaliação da concentração de flúor em águas minerais comercializadas no Brasil Evaluation of fluoride content of bottled drinking waters in Brazil - Rita S. Villena; Denise G. Borges; Jaime A. Cury (Universidade de São Paulo, 1996)
A utilização de flúor sistêmico deve ser controlada em termos de risco/benefício, pois enquanto a subdosagem não trouxer benefício anticárie, a sobredosagem estará associada com fluorose dental. Assim, uma das preocupações é o consumo de águas minerais, o qual tem aumentado nos últimos anos. Deste modo, foi realizado estudo com o objetivo de analisar a concentração de flúor em águas minerais comercializadas no Brasil. Foram analisadas 104 marcas comerciais, de diferentes regiões do País. Utilizou-se eletrodo específico Orion 96-09 e analisador de íons Orion EA 940, previamente calibrados com soluções padrões de flúor. Foram observadas concentrações de flúor variando de 0,0 a 4,4 ppm. Constataram-se: 1) Concentrações significativas de flúor não relatadas pelo produtor; 2) Concentrações de flúor sem significado preventivo anti-cárie, embora o produtor destaque na embalagem "Água Mineral Fluoretada"; 3) Concentrações de flúor capazes de provocar fluorose dental severa, embora o produtor não faça nenhuma referência que o mesmo existe. Conclui-se ser necessário um Sistema de Vigilância Sanitária para o controle de flúor nas águas minerais oferecidas à população brasileira, quer seja em termos de benefício como de risco. The utilization of a systemic fluoride method must be controlled in terms of risks and benefits. The reason for this is that while a small dose will not be effective in preventing dental caries, a larger dose may cause dental fluorosis. Therefore the knowledge of the fluoride concentration found in the bottled mineral waters sold throughout the Brazilian market the consumption of which has increased lately, is of great concern. The objective of the study was the analysis of the concentration of fluoride found in the bottled mineral waters. A hundred and four brands coming from different regions of Brazil were analysed using an Orion 96-09 ion specific electrode and an Orion EA 940 ionanalyser, previously calibrated with standard fluoride solutions. Different concentrations of fluoride ranging from 0.0 to 4.4 were found. It was discovered that specific bottled waters contained: 1) Significant concentrations of fluoride not reported by the producer; 2) Fluoride concentrations of no preventive effect, although the producer had advertised the water as a Fluoridated Mineral Water; 3) Fluoride concentrations high enough to cause dental fluorosis, although the producer did not alert the consumer to this fact. It is to be concluded, therefore, that a sanitary regulatory system for the control of the level of fluoride in the bottled mineral waters marketed is necessary. Such reputation should be formulated in terms of benefits as well as in terms of risks.